An Analysis of Lexical Relations Found in The Purple Heart Movie 2022 (Semantics Analysis) - Rina, Rina; Magria, Vera; Oktariza, Dodi (Krinok:Jurnal Linguistik Budaya, 2024)
This research analyzes the types of Lexical Relations found in the Purple Heart Movie.Lexical Relations is a branch of Semantics that focuses on the meaning of word. Lexical Relations describe the meaning of words in relation to other words. There are eight of Lexical Relations such as : homonymy, polysemy, synonymy, opposites (Antonymy), hyponymy, meronymy, member-collection and portion-mass. The objectives of this research are (1) To identify the types of Lexical Relations that found in the Purple Heart movie. This analysis is based on the theory by Saaed (2003) by explain eight types of Lexical Relations.The researcher used the descriptive qualitative method because this research aimed to describe the meaning of the word from utterances on movie that spoken by characters. Pictures are also used to present the result and to make it easier for readers to understand.The result of the research reveals some findings: There are 57 data the researcher collected from utterances used by characters in Purple Heart movie. Such as 4 homonymy,15 Polysemy,7 synonymy,13 opposites (antonymy),6 hyponymy, 3 meronymy, 4 member-collection and 5 portion-mass in the dialogue of Purple Heart movie. Then, the researcher found the dominant of types Lexical Relations of this research is 15 Polysemy from 57 data total.